Comparison of affinity ranking and immunochemical key data as measure for molecular antibody evolution. Issue 2 (2003) - Kramer Kramer, Karl Karl; Rau Rau, Doris Doris; Hock Hock, Bertold Bertold
Abstract : The evolutionary optimization of antibody binding properties in vitro opens new perspectives for immunochemistry, since the affinity and selectivity of a given antibody molecule can be tailored to meet the requirements of the envisaged analytical application. An efficient strategy for molecular antibody evolution is described that combines randomized point mutations and sequential recombination of variable antibody gene repertoires employing a group-selective library. This strategy enabled significant improvements in the binding of the model analyte atrazine that were monitored by both, kinetic measurements by the optical sensor BIAcore 2000 TM and immunochemical key data obtained by enzyme-linked immunosorbent assay (ELISA). The KD of the template antibody IPR-7 was improved by a factor of 17 from 1.27×10 –8 M to 7.46×10 –10 M for the optimized variant IPR-83. The enhanced KD is well in line with the 15 fold lowered IC50 of the atrazine ELISA, which was shifted from 13.6 µg/l for IPR-7 to 0.9 µg/l for IPR-83. Once the analytical properties of antibody fragments are optimized, antibody functionality can be tailored for specific technical demands, e.g. the directed immobilization on microchip surfaces. As an example, the variable region encoding genes of the scFv variants were subcloned into the Fab fragment expression vector pASK99, in order to reconstitute the antigen binding site of native antibody molecules. The expressed Fab fragments provide a C-terminal affinity tag for functionalized sensor surfaces. Again, the evaluation by ELISA as well as by BIAcore revealed a consistent ratio of analyte binding enhancement for the engineered Fab fragments.